Question
upstudy study bank question image url

\( \quad(v-7)^{2}=2 v^{2}-8 v+54 \) If there is more than one solution, separate them with commas.

Ask by Griffiths Bolton. in the United States
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( v = -1 \) and \( v = -5 \).

Solution

To solve the equation (v - 7)² = 2v² - 8v + 54, follow these steps: 1. Expand the left-hand side:   (v - 7)² = v² - 14v + 49 2. Substitute back into the equation:   v² - 14v + 49 = 2v² - 8v + 54 3. Bring all terms to one side:   0 = 2v² - 8v + 54 - (v² - 14v + 49)   0 = (2v² - v²) + (-8v + 14v) + (54 - 49)   0 = v² + 6v + 5 4. Factor the quadratic:   v² + 6v + 5 = (v + 1)(v + 5) = 0 5. Set each factor equal to zero:   v + 1 = 0 ⟹ v = -1   v + 5 = 0 ⟹ v = -5 Thus, the solutions are v = -1, -5.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( (v-7)^{2} = 2v^{2} - 8v + 54 \), we first expand the left side: \[ (v - 7)^2 = v^2 - 14v + 49 \] Now, we can rewrite the equation as: \[ v^2 - 14v + 49 = 2v^2 - 8v + 54 \] Next, we will move all terms to one side: \[ 0 = 2v^2 - 8v + 54 - v^2 + 14v - 49 \] This simplifies to: \[ 0 = v^2 + 6v + 5 \] Now, we can factor the quadratic: \[ 0 = (v + 5)(v + 1) \] Setting each factor to zero gives us the solutions: \[ v + 5 = 0 \quad \Rightarrow \quad v = -5 \] \[ v + 1 = 0 \quad \Rightarrow \quad v = -1 \] Thus, the solutions to the equation are \( v = -5, -1 \).

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy